2005
DOI: 10.1021/jp050056l
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of All Sites for Ti Substitution in Zeolite TS-1 by an Accurate Embedded-Cluster Method

Abstract: We studied the preferential location of Ti centers in the framework of the Ti-containing MFI zeolite TS-1 using a hybrid DFT/MM embedding method developed recently. This "covalent elastic polarizable environment" (covEPE) cluster embedding allows a complete and self-consistent treatment of solid covalent systems such as zeolites. For the present study, we used a gradient-corrected density functional approach. The resulting structural features of both Si- and Ti-substituted forms of the zeolite framework fit we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 61 publications
2
66
0
Order By: Relevance
“…It has also been hypothesized that Sn can form paired sites across six-membered rings in Beta topology, which may enhance the Lewis acidity compared with other framework topologies (13,39). Computational studies (42)(43)(44)(45)(46)(47)(48)(49), as well as experimental investigations using neutron diffraction (50-52) and synchrotron radiation X-ray diffraction (XRD) (53, 54) of Ti-MFI, have not shown consistent results on Ti siting. Deka et al (49) proposed that these experimental discrepancies are due mainly to kinetic effects caused by differences in synthesis conditions between research groups.…”
Section: Figurementioning
confidence: 99%
“…It has also been hypothesized that Sn can form paired sites across six-membered rings in Beta topology, which may enhance the Lewis acidity compared with other framework topologies (13,39). Computational studies (42)(43)(44)(45)(46)(47)(48)(49), as well as experimental investigations using neutron diffraction (50-52) and synchrotron radiation X-ray diffraction (XRD) (53, 54) of Ti-MFI, have not shown consistent results on Ti siting. Deka et al (49) proposed that these experimental discrepancies are due mainly to kinetic effects caused by differences in synthesis conditions between research groups.…”
Section: Figurementioning
confidence: 99%
“…There is abundant information on the distributions of triand tetravalent ions (e.g., B, Al, and Ti) in MFI-type zeolites. [16][17][18][19][20][21][22][23][24][25][26][27] Recently, the Al locations in MCM-22 zeolite were studied by Corma et al and our group. [28][29][30] It was found that these ions are not equally distributed among the various T sites.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] It was found that these ions are not equally distributed among the various T sites. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Herein, density functional calculations were employed to determine the Ti IV distribution in MCM-22 zeolite. The design of isolated titanium dioxide (TiO 2 ) within zeolites is currently a research focus, [31] owing to the unique photocatalytic reactivity of the Ti III sites for a variety Abstract: Isolated Ti species in zeolites show unique catalytic activities for a variety of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…By this reason, the energy for substitution of Si by Ti in the 12 distinct T sites of MFI was estimated using embedded clusters containing 5 T atoms. 43 The obtained substitution energies suggest that incorporation of isolated Ti ions into MFI framework is energetically most favourable at the T12 position. A tentative evaluation of the Ti population of different crystallographic sites for a temperature of 448 K, typical for zeolite synthesis, yielded 71% at the T12 site, that is, if the Ti distribution in the framework was governed by thermodynamic stability of the final material, the experimental studies should observe Ti mainly at this position.…”
Section: Structure and Isomorphic Substitution Of T Atomsmentioning
confidence: 89%
“…For example protonic forms of faujasite, chabasite (CHA) and ZSM-5 zeolite were studied by covEPE method. The Modelling of the isomorphic substitution of Si by Ti in MFI structure 43 was also performed with the same method, which is related to the structure of TS-1 molecular sieves. The real material TS-1 is notable for its catalytic activity and selectivity in various oxidation reactions.…”
Section: Structure and Isomorphic Substitution Of T Atomsmentioning
confidence: 99%